Penerapan teknik pembenihan dan budidaya ikan baung di Desa Batu Belah, Kecamatan Kampar, Riau - Sukendi Sukendi; Thamrin Thamrin; Ridwan Manda Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
The purpose of this community service program (PKM) is to provide knowledge and technology on the techniques of hatchery and fish cultivation in Batu Belah Village, Kampar District especially in the Lele Sejahtera Hatchery Group and Mina Karya Fish Farming Group (Pokdakan). The method used in this PKM activity is the method of lectures, discussions and direct demonstrations in the field. The results of the evaluation show that there were changes in knowledge from 10 participants, members of the Prosperous People's Hatchery Group (KPR) known as seven people (70.00%) had been able to absorb the material given with a very good predicate, the other participants were in good and sufficient categories. Furthermore, of the 11 participants in the Mina Karya Fish Cultivation Group (Pokdakan) it was found that eight people (72.23%) had been able to absorb the material given in very good categories, the other participants were in the right and sufficient categories. The results of the evaluation of this skill show that the participants of the activity have been able to practice the material on hatchery through artificial spawning and Baung fish cultivation technology. Furthermore, the results of the impact evaluation are known to show that the impact of this PKM activity has been felt by the members of the two existing farming groups so that it can increase the income of the members of the two farmer groups, and at the same time improve their welfare.